A Study on the correlation between platelet indices and severity score in acute ischemic stroke - Dr. Dasari Govind; Dr. Mallipeddi Malleswara Rao; Dr. K. Sudheer (International Journal of Medical Research and Review, 2020)
Background: Acute ischemic stroke results from the sudden loss of blood circulation to an area of cerebral hemispheres leading to irreversible brain injury and neurological deficits persisting for more than 24 hours or until death. It accounts for 80-87% of all strokes. The present study aimed to find the association between various hematological indices such as Mean platelet Volume (MPV), Platelet Distribution Width (PDW), Platelet to Lymphocyte ratio (PLR), and National Institute of Health Stroke Scale (NIHSS).Methods: It was a prospective study done at the Department of Medicine at Great Eastern Medical School and Hospital in which 80 patients with Acute Ischemic stroke were divided into two groups basing on the NIHSS score. Proper Exclusion criteria were carried out and the patients' blood samples were taken. Various Platelet and hematological indices were measured and statistical analysis was done using SPSS Software.Results: There is a positive correlation between PLR and NIHSS scores. It is a statistically significant association. But there is no statistical significance between Platelet indices and NIHSS score.Conclusion: Being Low cost and easy to measure the nature of PLR, these indices can be used in the prediction of the prognosis in Acute Ischemic Stroke Patients.